Odontogenic Fibromyxoma of Maxilla: A Rare Case Report - G. Siva Prasad Reddy; B. Surya Kumar; Radhika Muppa; Shravan Kumar Regonda; Harish Kumar TVS (Hindawi Limited, 2013)
Fibromyxoma is a rare odontogenic tumour which is benign, but locally aggressive. The etiology of these tumours is unknown, but because of its limitation to the teeth bearing areas and occasional presence of odontogenic epithelial fragments within the tumour which suggest that it is of odontogenic origin. It is a slow growing painless tumour that frequently occurs in second and third decades of life. Females are more commonly affected than males. The tumour can cause gradual expansion of the cortical plates and cause loosening and displacement of teeth, although root resorption may be rare. The surgical treatment of these tumours consists of complete enucleation or radical excision. The aim of this paper is to present the rarity of a fibromyxoma of the maxilla.